Uncus Herniation Presenting as Immediate Onset Postoperative Hemichorea - Agarwal, Vinay; Singhal, Namit (Journal of Pediatric Neurology, 2020)
Chorea is defined as a state of excessive spontaneous movements, irregularly timed, nonrepetitive, randomly distributed, and abrupt in character. Thalamic and subthalamic lesions are commonly known to cause hemichorea. Here, we describe a patient with hydrocephalus due to aqueductal stenosis that caused hemichorea in the immediate postoperative period due to subthalamic infarct of uncus herniation. Considering that hydrocephalus symmetrically affects the central nervous system, the asymmetric presentation of chorea in the immediate postoperative period after wakening up from anesthesia could be confusing if a possibility of uncus herniation is not considered.
Keywords: hemichorea; subthalamic nucleus; uncus herniation; hydrocephalus